2006
DOI: 10.1121/1.2173068
|View full text |Cite
|
Sign up to set email alerts
|

The modeling of the radiation and response Green’s function of a fluid-loaded cylindrical shell with an external compliant layer

Abstract: Scattering and radiation of acoustic waves from a fluid-loaded cylindrical shell with an external compliant layer are of interest. The compliant layer can be modeled by a normally reacting impedance layer, which has the advantage that complex compliant layer geometries, such as partial compliant layers, can be considered. A question may, however, arise as to the accuracy of this approach. A more rigorous approach is to model the elastic shell and compliant layer using a multilayer shell theory, which has the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In the field of scattering of the cylindrical shell, Mitri (2006) used the Navier theory to study the scattering of the cylindrical shells by incident plane-progressive waves. Cuschieri (2005) dealt with the similar problem with two methods: the Navier theory and the mass/stiffness impedance equivalence method, and showed that the two approaches produced similar results, except for thickness resonances of the compliant layer. But in the two papers above, the incident wave was assumed as the plane waves, so the problem was simplified to a 2-D plane strain problem.…”
Section: Introductionmentioning
confidence: 77%
“…In the field of scattering of the cylindrical shell, Mitri (2006) used the Navier theory to study the scattering of the cylindrical shells by incident plane-progressive waves. Cuschieri (2005) dealt with the similar problem with two methods: the Navier theory and the mass/stiffness impedance equivalence method, and showed that the two approaches produced similar results, except for thickness resonances of the compliant layer. But in the two papers above, the incident wave was assumed as the plane waves, so the problem was simplified to a 2-D plane strain problem.…”
Section: Introductionmentioning
confidence: 77%